Corporate Governance dan Keputusan Pendanaan - Annisa Yasmin; Noorlaily Fitdiarini (Universitas Pendidikan Nasional, 2020)
This research aims to examine the influence of corporate governance on financing decisions or capital structures on manufacturing companies listed on the Indonesia Stock Exchange for the period 2008-2010. In this study, corporate governance was projected with board size, independent commissioner, managerial ownership, and institutional ownership, while funding decisions were projected with debt ratio. The technique used to test the influence of corporate governance on capital structures is using multiple linear regression analysis. The results found that board size and board composition have a significant negative effect on the capital structure, while managerial ownership, and institutional ownership do not have a significant influence on the capital structure.